2013
DOI: 10.1002/hed.23262
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting swallow outcome following treatment for advanced oral and oropharyngeal malignancies

Abstract: Swallow function recovery postsurgery is better in patients with higher FOIS presurgery, smaller tumors, and no requirement for radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 36 publications
(102 reference statements)
1
32
0
Order By: Relevance
“…A further study confirmed these findings, reporting that treated volume was an important predictor of weight loss regardless of clinical stage . Treatment for head and neck cancer, particularly chemoradiotherapy, has been found to cause dysphagia or increase the severity of an existing swallowing impairment . A recent systematic review reported the incidence of dysphagia was 22% to 62% posttreatment .…”
Section: Introductionmentioning
confidence: 72%
“…A further study confirmed these findings, reporting that treated volume was an important predictor of weight loss regardless of clinical stage . Treatment for head and neck cancer, particularly chemoradiotherapy, has been found to cause dysphagia or increase the severity of an existing swallowing impairment . A recent systematic review reported the incidence of dysphagia was 22% to 62% posttreatment .…”
Section: Introductionmentioning
confidence: 72%
“…It is completed and scored by a health‐care provider based on medical chart review, dietary journals, and/or patient report. Although the FOIS was validated for use within the stroke population, recent clinical trials have extended its use as a primary and secondary outcome measure to patients with head and neck cancer and in some trials it serves as a primary outcome of interest to index change in swallowing function …”
Section: Introductionmentioning
confidence: 99%
“…Long-term use of a gastrostomy tube is associated with a significant deterioration in quality of life. 11 A study by Kalavrezos et al 14 found an enteral feeding rate of about 5% after the treatment of locally advanced oral cavity and oropharynx cancer. However, as our study focused on severe swallowing disorders, our higher rate is to be expected, and this cannot be compared to a series dealing more generally with swallowing disorders.…”
Section: Discussionmentioning
confidence: 98%